Tamoxifen induces toxicity, causes autophagy, and partially reverses dexamethasone resistance in Jurkat T cells. Issue 5 (15th January 2019) - Torres‐López, Liliana; Maycotte, Paola; Liñán‐Rico, Andrómeda; Liñán‐Rico, Liliana; Donis‐Maturano, Luis; Delgado‐Enciso, Iván; Meza‐Robles, Carmen; Vásquez‐Jiménez, Clemente; Hernández‐Cruz, Arturo; Dobrovinskaya, Oxana
Abstract: Estrogens demonstrate biological activity in numerous organ systems, including the immune system, and exert their effects through estrogen receptors (ER) of two types: intracellular ERα and ERβ that activate transcriptional factors and membrane G protein‐coupled ER GPER. The latter is capable to mediate fast activation of cytosolic signaling pathways, influencing transcriptional events in response to estrogens. Tamoxifen (TAM), widely used in chemotherapy of ERα‐positive breast cancer, is considered as an ERα antagonist and GPER agonist. TAM was shown to possess "off‐target" cytotoxicity, not related to ER in various tumor types. The present work was designed to study biological effects of TAM on the glucocorticoid (GC)‐resistant cell line Jurkat, derived from acute lymphoblastic leukemia of T lineage (T‐ALL). We have shown that T‐ALL cell lines, in contrast to healthy T cells, express only GPER, but not ERα or ERβ. TAM compromised mitochondrial function and reduced the viability and proliferation of Jurkat cells. Additionally, TAM induced autophagy in a GPER‐dependent manner. Gene expression profiling revealed the up‐regulation of autophagy‐related gene ATG5 . Interestingly, TAM sensitized Jurkat cells to dexamethasone (DEX) treatment, which may be related to its capacity to cause autophagy. We suggest that TAM‐based adjuvant therapy may represent a novel strategy in T‐ALL patients handling. Abstract : GPER‐mediated TAM‐induced autophagy sensitizes GC‐resistant Jurkat cells to DEX.